The effect of service, quality of goods and prices on customer satisfaction at Ayu Store - Ayu Parlinda Lestari; Basar Maringan Hutauruk (Junal Ilmu Manajemen, 2023)
This study aims to determine the partial and simultaneous effect of service, quality of goods and prices on consumer satisfaction at Ayu store. The research method in this study uses a quantitative approach in which this study describes the relationship of influencing and being influenced by the variables to be studied which can be interpreted as a research method based on the philosophy of positivism. The population in this study are Ayu store consumers. The sample in this study were 100 respondents. The sampling method in this study used a simple random sampling method. Simple random sampling technique is a technique of taking samples from members of the population which is done randomly without regard to the strata in the population. Based on the results of the study, service has a positive and significant effect on consumer satisfaction at Ayu store, quality of goods has a positive and significant effect on customer satisfaction at Ayu store, price has a positive and significant effect on customer satisfaction at Ayu store and simultaneously service, quality of goods and price have an effect and significant to consumer satisfaction Ayu store.